2013
DOI: 10.1158/1078-0432.ccr-12-2241
|View full text |Cite
|
Sign up to set email alerts
|

Does Microenvironment Contribute to the Etiology of Estrogen Receptor–Negative Breast Cancer?

Abstract: What dictates the prevalence of certain types of breast cancer, which are classified by markers, particularly estrogen receptor (ER), expression profiles such as basal or luminal, and genetic alterations such as HER2 amplification, in particular populations is not well understood. It is increasingly evident that microenvironment disruption is highly intertwined with cancer progression. Here, the idea that microenvironment shapes the course of carcinogenesis, and hence breast cancer subtype, is discussed. Aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 82 publications
1
23
1
Order By: Relevance
“…Supporting results of an increased risk of HER2-positive breast cancer after exposure to ionizing radiation were also found in several other recent studies. 24,25,28,29 In a review by Barcellos-Hof, 26 it was postulated that radiation predisposes ER-negative breast tumors, which is in contrast to our results where occupational exposure to ionizing radiation led to a slight increase in ER-positive breast cancer.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Supporting results of an increased risk of HER2-positive breast cancer after exposure to ionizing radiation were also found in several other recent studies. 24,25,28,29 In a review by Barcellos-Hof, 26 it was postulated that radiation predisposes ER-negative breast tumors, which is in contrast to our results where occupational exposure to ionizing radiation led to a slight increase in ER-positive breast cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…23 Gene amplification of human epidermal growth factor receptor 2 (HER2) and estrogen receptor (ER)-negative breast tumors are seen in breast cancers caused by radiation exposure. [24][25][26][27][28][29] Human epidermal growth factor receptor 2 is involved in pathways that regulate cell growth and proliferation. 30 Estrogens are believed to affect the pathological processes initiated by ionizing radiation in turning mammary gland cells into malignant cells.…”
mentioning
confidence: 99%
“…ERa-negative breast cancers comprise w30% of all breast cancers and are typically more aggressive and have poor survival prognoses compared with ERa-positive tumours (Barcellos-Hoff 2013). AR expression in ERa-negative breast cancer is correlated with a lower Nottingham grade and apocrine differentiation (Niemeier et al 2010).…”
Section: Era-negative Breast Cancermentioning
confidence: 99%
“…1,2 Among the breast cancer subtypes, estrogen receptor α (ER)-negative breast cancers are more aggressive and metastatic than ER-positive breast cancers and unresponsive to anti-estrogen therapy. 3 Elevated expression of human epidermal growth factor receptor 2 (HER2), which activates the mitogen-activated protein kinase (MAPK) signaling pathways, is also associated with aggressiveness and metastasis in breast cancer. 4 It has been shown that ER-positive and -negative breast cancers exhibit large differences in their gene expression profiles.…”
Section: Introductionmentioning
confidence: 99%